The importance of district heating systems in periods of energy crisis: Case study for the city of Skopje - Shesho, Igor; Uler-Zefikj, Monika; Filkoski, Risto; Tashevski, Done (University Library in Kragujevac, 2022)
Nowadays energy crises are characterized by their intensity, i.e. for a short period of time they can cause significant consequences on the economy and overall living. The impacts of energy crisis are mainly reflected indirectly through misbalance in electrical energy production, which is main component and foundation for all socio-economic processes. In addition, the current coincidence of the energy crisis (high price of natural gas) with the heating season reveals and emphasizes the importance of the heating energy. The aim of this paper is to analyse the role, advantages and disadvantages of existing district heating (DH) systems with cogeneration power plants CHP), as an important link in the country power system, especially in times of energy crises. In the analyses as a reference system is considered the DH system in Skopje, Republic of North Macedonia. Assessment for the influence of the fluctuation in heat consumption in the DH system on the power system is performed by using simulation software for energy modelling of the district heating system in Skopje, linked with the data for yearly (hourly basis) electricity consumption. Additional economic assessment is conducted to determine cost competitiveness of DH system with other individual heating technologies available in urban areas. Results reveal that district heating systems with cogeneration power plants in densely populated urban areas are cost optimal heating system and extremely important link in country energy chain, providing energy stability, along with potential consequences in case of longer (un) foreseen interruptions in operation.